2014
DOI: 10.1002/fsn3.109
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanisms of 8‐prenylnaringenin on osteoblast MC3T3‐E1 and osteoclast‐like cells RAW264.7

Abstract: 8-Prenylnaringenin (8-PN) is a phytoestrogen with the highest estrogenic activity. The objective of the present study was to confirm the superiority of 8-PN on bone metabolisms and the estrogen receptor (ER) subtype mediating effects of 8-PN. The osteoblast MC3T3-E1 and osteoclast-like cell line RAW264.7 were treated with 17β-estradiol (10−8 mol/L), genistein (10−5 mol/L), daidzein (10−5 mol/L), 8-PN (10−5 mol/L) alone or in the presence of ERα antagonist MPP (10−7 mol/L) and ERβ antagonist PTHPP (1.5 × 10−7 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…The histological analyses of tibial sections yielded significant lower numbers of osteoclasts in the hops group, thus comparable to that reduction induced by E 2 benzoate (Table 2). Our results are similar to two in vitro studies that described 8-PN-induced reduction of the osteoclast number by decreasing osteoclast formation and increasing apoptosis as well as by diminishing osteoclast differentiation (Luo et al, 2014; Ming et al, 2013). To our knowledge, this is the first time that the effect of a standardized hops extract on osteoclast number has been shown in vivo .…”
Section: Discussionsupporting
confidence: 91%
“…The histological analyses of tibial sections yielded significant lower numbers of osteoclasts in the hops group, thus comparable to that reduction induced by E 2 benzoate (Table 2). Our results are similar to two in vitro studies that described 8-PN-induced reduction of the osteoclast number by decreasing osteoclast formation and increasing apoptosis as well as by diminishing osteoclast differentiation (Luo et al, 2014; Ming et al, 2013). To our knowledge, this is the first time that the effect of a standardized hops extract on osteoclast number has been shown in vivo .…”
Section: Discussionsupporting
confidence: 91%
“…Examples include several phytoestrogens, including genistein [27,28], daizein [29], and 8-prenylnaringenin [30], and other flavonoids, such as resveratrol [31,32], quercitrin [33,34], and fisetin [10,35]. Thus, cafestol seems to have dual effects on bone cells, such as the inhibition of OCL differentiation and the promotion of OBL differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that natural compounds have dual effects on bone cells, such as the inhibition of OCL differentiation and promotion of OBL differentiation. Examples include several phytoestrogens, including genistein [27,28], daizein [29], and 8-prenylnaringenin [30], and other flavonoids, such as resveratrol [31,32], quercitrin [33,34], and fisetin [10,35]. The dual effects of phytoestrogens (genistein, daizein, and 8-prenylnaringenin) on OCLs and OBL are thought to be due to the inhibition of estrogen receptor-mediated events, whereas those of other flavonoids (resveratrol, quercetin, and fisetin) are mediated by antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…RAW264.7 cell linage is well-characterized with regard to macrophage-mediated immune, metabolic and phagocytic functions 21 and is increasingly used and accepted as a cellular model of osteoclastogenic study; [24][25][26] however, with the vastly usage of RAW-OCs for understanding the osteocalstogenesis in the past two decades, there raised considerable requirements for the extensively understanding the RAW-OCs and associated cellular biological mechanisms. [29][30][31] Considering RAW264. [29][30][31] Considering RAW264.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 On the other hand, document studies reported that during the osteoclastic induction, various stimuli might lead different cellular fates during the RAW-OC induction. [29][30][31] Considering RAW264.7 cell-derived osteoclasts have not yet been well-characterized, and RAW264.7 cells are polymorphic with respect to the phenotype of the individual cells comprising this cell line and different results associated with various stimuli contributions. [32][33][34][35] Therefore, in our present review, we will summarize the current knowledge of the phenotype of RAW264.7 cells and the current understanding of complicated interactions between various stimuli and RAW-OCs in the light of the recent progress in this field.…”
Section: Introductionmentioning
confidence: 99%